Frost Heaving Properties of Gravelly Soils in Alpine Seasonally Frozen Regions - Cheng Chen; Zhigang Zhang; Li Ling; Baoyuan He; Yanjia Jiang; Zhihe Cheng (Advances in Materials Science and Engineering)
To investigate the frost heaving properties of gravelly soil in alpine seasonally frozen regions and provide a foundation for the antifrost heaving design of the foundation tower in the Manzhouli 500 kV electrical transmission line. First, particle analysis and compaction tests were used to assess the basic characteristics of gravelly soil. Then, to investigate, a unidirectional freezing test of graded sand was performed to analyze the regularity and properties of the frozen process of graded sand. The test results demonstrate that the temperature gradient and the number of freeze-thaw cycles considerably affect the freezing of graded sand. The greater the temperature gradient and the number of freeze-thaw cycles, the greater the frost heave. In the freezing process, graded sand with zero fine-grain content exhibits obvious freezing shrinkage and thawing settlement. Still, the frost heave of sand is small. The frozen damage of graded sand is not caused by frost heaving deformation but by the deterioration of soil structure and the decrease of bearing capacity under hydrothermal coupling. Finally, experimental research is used to propose prevention and control measures for frost heave of power transmission and transformation projects.